Effect of Used Motor Oil and Bitumen as Additive on the Permeability and Mechanical Properties of Low Plastic Soil - Kamran Iqbal; Chengshun Xu; Hassan Nasir; Muhammad Alam; Asim Farooq; Edward J. Williams (Advances in Materials Science and Engineering)
Stability of permeable soils near large-scale water reservoirs for paved and unpaved road pavements is all too frequently compromised due to excessive seepage and the climatic conditions of that area. In this research, a multilevel research approach was adopted by conducting a comparative study of the microspectroscopy through Fourier transform infrared (FTIR) spectra to investigate the maximum absorbance correlation along with mechanical investigations (such as the compressive strength, modified proctor test, California bearing ratio test, and swell percentage test). The native low plastic soil sample (CL) was blended with varying percentages of petroleum additives (bitumen and used motor oil) independently at 0%, 4%, 8%, 12%, 16%, and 20%. A comparison of results in the case of bitumen and used motor oil revealed that a decrease in Atterberg’s limits occurred accompanied by an increase of bitumen blending percentage, while used motor oil (UMO) increased the plastic limit. Maximum dry density (MDD) increases while optimum moisture content (OMC) decreases with the increase in bitumen. Used motor oil (UMO) initially (up to 4%) increased the MDD and subsequently decreased it. Investigative reports show that bitumen causes a decrease in swell percentage and increases California bearing ratio (CBR), whereas UMO causes a continuous increase in percentage swell and decrease in CBR. The addition of bitumen in soil resulted in a decrease in the coefficient of permeability (k), while UMO has a significant result of up to 4%. Regarding the control sample, spectrum analysis through FTIR effectively supports the laboratory results as the intensity of peaks increases with the oil, and bitumen concentration reveals that oil and bitumen impart cementitious property to the soil. Moreover, this research work by experiment supported and strengthened the idea of soil pavement stabilization through bitumen, which gives antiwater stability, and facilitates low-cost construction by obtaining raw material on the spot. UMO adversely affects soil properties beyond 4% addition by weight.